Microwave-controlled all-solid-state lithium battery
Through microwave control technology, heating all-solid-state lithium batteries and combining with specific electrode material design, the problem of the battery not being able to charge and discharge normally at temperatures below 60℃ is solved, achieving higher charge and discharge efficiency and a wider operating temperature range.
Patent Information
- Application Number
- CN202510299785.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-06-24
AI Technical Summary
All-solid-state lithium batteries cannot charge and discharge normally at temperatures below 60°C, and the charge and discharge efficiency is low, resulting in energy discharge in the form of thermal energy.
Microwave control technology is used to heat all-solid lithium batteries, increase their internal temperature, and optimize the chemical reaction process of the battery through specific electrode materials and structural designs, including graphene positive electrode film and lithium silicide ceramic powder.
It realizes normal charging and discharging of all-solid-state lithium batteries at lower temperatures (-10℃~105℃), improves charging and discharging efficiency, reduces thermal energy emissions, and enhances the safety of the battery.
Abstract
Description
Technical Field:
[0001] The present invention relates to a microwave-controlled all-solid-state lithium battery.
[0002] Background Art:
[0003] All-solid-state lithium batteries need to operate at temperatures above 60 °C to enable normal charge and discharge chemical reactions and can support high-current charge and discharge. At temperatures below 60 °C, all-solid-state lithium batteries cannot carry out normal charge and discharge chemical reactions and can only support low-current charge and discharge. The low-current charge and discharge of all-solid-state lithium batteries cause the temperature of the solid-state lithium battery to rise. Only when the temperature of the all-solid-state lithium battery rises above 60 °C can normal charge and discharge chemical reactions occur and high-current charge and discharge be supported. The charging and discharging efficiency of all-solid-state lithium batteries is 50%, and the remaining energy is dissipated as heat. The phosphorus sulfide in the phosphorus sulfide solid-state lithium battery slowly reacts with water at 30 °C. The phosphorus sulfide solid-state lithium battery can be used at temperatures below -0 °C. When the phosphorus sulfide in the phosphorus sulfide solid-state lithium battery is exposed to air at temperatures above 39 °C, it slowly reacts with oxygen in the air.
[0004] Metallic lithium is the negative electrode material of traditional ion lithium batteries. Lithium silicide ceramic powder is the negative electrode material of all-solid-state phosphorus sulfide lithium batteries. The phosphorus sulfide solid electrolyte containing lithium iodide is the positive electrode material of all-solid-state phosphorus sulfide lithium batteries. The amount of lithium used in all-solid-state lithium batteries with the same output power is [times] that of lithium in traditional ion lithium batteries. Summary of the Invention:
[0005] It should be noted that there seems to be an unclear expression "times" in the text of item . You may need to check and correct it according to the actual situation.A microwave-controlled all-solid-state lithium battery. The all-solid-state lithium sulfide phosphorus battery from bottom to top successively consists of a graphene positive electrode film, the first layer of lithium iodide-containing phosphorus sulfide powder, the first layer of lithium silicide ceramic powder, the first layer of graphene film, the second layer of lithium iodide-containing phosphorus sulfide powder, the second layer of lithium silicide ceramic powder, the second layer of graphene film, the third layer of lithium iodide-containing phosphorus sulfide powder, the third layer of lithium silicide ceramic powder, the third layer of graphene film, the fourth layer of lithium iodide-containing phosphorus sulfide powder, the fourth layer of lithium silicide ceramic powder, the fourth layer of graphene film, the fifth layer of lithium iodide-containing phosphorus sulfide powder, the fifth layer of lithium silicide ceramic powder, and a graphene negative electrode film. The graphene electrode lead-out component consists of a solid graphene plate, a solid graphene rod, a carbon fiber braided tube, graphene powder, an insulating sleeve, and a solid graphene plug. The size of the solid graphene plate is the same as that of the graphene positive electrode film or the graphene negative electrode film. The edge of the solid graphene plate is connected to the solid graphene rod. One end of the carbon fiber braided tube is fixed to the graphene rod. The carbon fiber braided tube is filled with graphene powder. An insulating sleeve is sleeved outside the carbon fiber braided tube. The tip of the solid graphene plug is inserted into the other end of the carbon fiber braided tube. The upper surface borders of the graphene positive electrode film, the first layer of graphene film, the second layer of graphene film, the third layer of graphene film, and the fourth layer of graphene film are all coated with uncured butyl benzene rubber. The lower surface borders of the first layer of graphene film, the second layer of graphene film, the third layer of graphene film, the fourth layer of graphene film, and the graphene negative electrode film are all coated with uncured butyl benzene rubber. The lithium iodide-containing phosphorus sulfide solid electrolyte is the positive electrode material of the all-solid-state lithium sulfide phosphorus battery, and the lithium silicide ceramic powder is the negative electrode material of the all-solid-state sulfur lithium sulfide phosphorus battery. The solid sulfur lithium battery is heated to 150 °C to cure the uncured butyl benzene rubber. The all-solid-state lithium sulfide phosphorus battery can be normally charged and discharged at 60 °C. The operating range of the all-solid-state lithium sulfide phosphorus battery is -10 °C to 105 °C. The all-solid-state lithium sulfide phosphorus battery is in a metal container on the car chassis. One end of the metal container on the car chassis has an air inlet window, and a stainless steel wire mesh is installed on the air inlet window. The air duct connected from the blower is connected to the air inlet window; the other end of the metal container on the car chassis has an air outlet window, and a stainless steel wire mesh is installed on the air outlet window, and an air outlet duct is installed on the air outlet window. The top of the metal container on the car chassis is equipped with a glass sandwich, and the blades of an electric microwave stirrer are inside the glass sandwich installed on the top of the metal container on the car chassis. Microwaves are introduced into the metal container on the car chassis containing the all-solid-state lithium sulfide phosphorus battery before charging and discharging to control the chemical reactions inside the all-solid-state lithium sulfide phosphorus battery and increase the internal temperature of the all-solid-state lithium sulfide phosphorus battery.
[0006] A microwave-controlled all-solid-state lithium battery. Ethanol is used to blend a powder containing 5% lithium iodide and 95% phosphorus sulfide to form a phosphorus sulfide slurry containing lithium iodide. Lithium iodide can reduce the internal resistance of the all-solid-state lithium sulfur-phosphorus sulfide battery. Ethanol is used to blend lithium silicide ceramic powder to form a lithium silicide ceramic slurry. A layer of phosphorus sulfide slurry containing lithium iodide is coated on the upper surface of the graphene positive electrode film, the upper surface of the first graphene film, the upper surface of the second graphene film, the upper surface of the third graphene film, and the upper surface of the fourth graphene film. A layer of butylbenzene rubber raw material is coated on the upper surface border of the graphene positive electrode film, the upper surface border of the first graphene film, the upper surface border of the second graphene film, the upper surface border of the third graphene film, and the upper surface border of the fourth graphene film. A layer of lithium silicide ceramic slurry is coated on the lower surface of the first graphene film, the lower surface of the second graphene film, the lower surface of the third graphene film, the lower surface of the fourth graphene film, and the lower surface of the graphene negative electrode film. The graphene positive electrode film, the first graphene film, the second graphene film, the third graphene film, the fourth graphene film, and the graphene positive electrode film are stacked and bonded together, and heated to 150 °C to cure the butylbenzene rubber raw material and evaporate the ethanol, forming an all-solid-state phosphorus sulfide lithium battery. Several all-solid-state phosphorus sulfide lithium batteries are adhesively stacked together with epoxy resin to form a group of all-solid-state phosphorus sulfide lithium batteries. Fabricate a graphene electrode lead-out component: Mix graphene powder with an organic binder and place it in a mold. Heat the mold and extrude the graphene powder in the mold. After cooling, take out the solid graphene plate with a solid graphene rod. Coat the inner surface of one end of a carbon fiber braided tube with a layer of epoxy resin, then slip this end over the solid graphene rod and heat to cure. Then fill the carbon fiber braided tube with graphene powder and compact it. Insert the tip of a solid graphene plug adhesively bonded with epoxy resin into the other end of the carbon fiber braided tube. Finally, slip an insulating sleeve over the carbon fiber braided tube to form the graphene electrode lead-out component. Use epoxy resin to bond the solid graphene plate of a graphene electrode lead-out component under the graphene positive electrode film of the lowermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries, and use epoxy resin to bond the solid graphene plate of a graphene electrode lead-out component above the graphene negative electrode film of the uppermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries, and then heat to cure. Before charging and discharging, microwave is introduced into the metal container of the vehicle chassis containing the all-solid-state phosphorus sulfide lithium battery. The blades of the electric microwave stirrer in the glass sandwich on the top of the vehicle chassis metal container rotate to stir the microwave and stir the microwave in the vehicle chassis metal container. The air blown by the blower enters the vehicle chassis metal container, stirs the microwave in the vehicle chassis metal container, and cools the all-solid-state lithium battery in the vehicle chassis metal container. The microwave controls the chemical reactions inside the all-solid-state phosphorus sulfide lithium battery and raises the temperature inside the all-solid-state phosphorus sulfide lithium battery.The chemical reaction process of charging and discharging a all-solid-state lithium battery is a process of electron transfer. Microwaves will cause electrons to oscillate during movement, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. Just like the extrusion piles used in infrastructure construction, not only pressure but also vibration needs to be applied to the piles so that they can be smoothly inserted into the soil. The graphene film of the all-solid-state lithium battery has a large number of free electrons, which oscillate under the action of microwaves to generate heat. The internal temperature of the all-solid-state lithium battery rises, and the internal energy of various substances in the all-solid-state lithium battery increases, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. The lithium atoms in the lithium silicide ceramic are in-situ solidified, and the lithium atoms in the lithium silicide ceramic will not break away from the bondage of silicon atoms during the chemical reaction process. The all-solid-state lithium sulfide phosphorus battery can be normally charged and discharged at 60°C, and the operating range of the all-solid-state lithium sulfide phosphorus battery is -10°C to 105°C. The phosphorus sulfide in the phosphorus sulfide solid-state lithium battery slowly reacts with oxygen in the air when exposed to air above 39°C. Therefore, the all-solid-state sulfur phosphorus sulfide lithium battery can be charged and discharged with a small current at low temperatures.
[0007] A microwave-controlled all-solid-state lithium battery. The all-solid-state sulfur and phosphorus sulfide lithium battery from bottom to top in sequence is a graphene positive electrode film, the first layer of powder containing lithium iodide and phosphorus sulfide, the first layer of lithium silicide ceramic powder, the first layer of graphene film, the second layer of powder containing lithium iodide and phosphorus sulfide, the second layer of lithium silicide ceramic powder, the second layer of graphene film, the third layer of powder containing lithium iodide and phosphorus sulfide, the third layer of lithium silicide ceramic powder, the third layer of graphene film, the fourth layer of powder containing lithium iodide and phosphorus sulfide, the fourth layer of lithium silicide ceramic powder, the fourth layer of graphene film, the fifth layer of powder containing lithium iodide and phosphorus sulfide, the fifth layer of lithium silicide ceramic powder, and a graphene negative electrode film. The graphene electrode lead-out component is composed of a solid graphene plate, a solid graphene rod, a carbon fiber braided tube, graphene powder, an insulating sleeve, and a solid graphene plug. The size of the solid graphene plate is the same as that of the graphene positive electrode film or the graphene negative electrode film. The edge of the solid graphene plate is connected to the solid graphene rod. One end of the carbon fiber braided tube is fixed on the graphene rod. The carbon fiber braided tube is filled with graphene powder. An insulating sleeve is sleeved outside the carbon fiber braided tube. The tip of the solid graphene plug is inserted into the other end of the carbon fiber braided tube. The upper surface borders of the graphene positive electrode film, the upper surface borders of the first layer of graphene film, the upper surface borders of the second layer of graphene film, the upper surface borders of the third layer of graphene film, and the upper surface borders of the fourth layer of graphene film are all coated with raw butyl benzene rubber. The lower surface borders of the first layer of graphene film, the lower surface borders of the second layer of graphene film, the lower surface borders of the third layer of graphene film, the lower surface borders of the fourth layer of graphene film, and the lower surface border of the graphene negative electrode film are all coated with raw butyl benzene rubber. The solid electrolyte containing lithium iodide and phosphorus sulfide is the positive electrode material of the all-solid-state phosphorus sulfide lithium battery. The lithium silicide ceramic powder is the negative electrode material of the all-solid-state sulfur and phosphorus sulfide lithium battery. The solid sulfur lithium battery is heated to 150°C to cure the raw butyl benzene rubber; the all-solid-state sulfur and phosphorus sulfide lithium battery can be normally charged and discharged at 60°C. The operating range of the all-solid-state sulfur and phosphorus sulfide lithium battery is from -10°C to 105°C. The all-solid-state sulfur and phosphorus sulfide lithium battery is in a metal container on the vehicle chassis. One end of the metal container on the vehicle chassis has an air inlet window, and a stainless steel wire mesh is installed on the air inlet window. The air duct connected from the blower is connected to the air inlet window water; the other end of the metal container on the vehicle chassis has an air outlet window, and a stainless steel wire mesh is installed on the air outlet window. An air outlet duct is installed on the air outlet window. The positive electrode material of the all-solid-state phosphorus sulfide lithium battery is the sulfur solid electrolyte containing lithium iodide and phosphorus sulfide. The top of the metal container on the vehicle chassis is equipped with a glass sandwich, and the blades of an electric microwave stirrer are in the glass sandwich installed on the top of the metal container on the vehicle chassis. Microwaves are introduced into the metal container on the vehicle chassis containing the all-solid-state sulfur and phosphorus sulfide lithium battery before charging and discharging, which is used to control the chemical reaction inside the all-solid-state sulfur and phosphorus sulfide lithium battery and to increase the temperature inside the all-solid-state sulfur and phosphorus sulfide lithium battery.
[0008] A microwave-controlled all-solid-state lithium battery. Ethanol is used to blend sulfur powder containing 5% lithium iodide and 20% phosphorus sulfide and 70% sulfur to form a sulfur slurry containing lithium iodide and phosphorus sulfide. Lithium iodide can reduce the internal resistance of the all-solid-state sulfur-phosphorus sulfide lithium battery. Ethanol is used to blend lithium silicide ceramic powder to form a lithium silicide ceramic slurry. A layer of sulfur slurry containing lithium iodide and phosphorus sulfide is coated on the upper surface of the graphene positive electrode film, the upper surface of the first graphene film, the upper surface of the second graphene film, the upper surface of the third graphene film, and the upper surface of the fourth graphene film. A layer of butylbenzene rubber raw material is coated on the upper surface frame of the graphene positive electrode film, the upper surface frame of the first graphene film, the upper surface frame of the second graphene film, the upper surface frame of the third graphene film, and the upper surface frame of the fourth graphene film. A layer of lithium silicide ceramic slurry is coated on the lower surface of the first graphene film, the lower surface of the second graphene film, the lower surface of the third graphene film, the lower surface of the fourth graphene film, and the lower surface of the graphene negative electrode film. The graphene positive electrode film, the first graphene film, the second graphene film, the third graphene film, the fourth graphene film, and the graphene positive electrode film are stacked and bonded together, and heated to 150 °C to cure the butylbenzene rubber raw material and vaporize the ethanol and overflow, becoming an all-solid-state sulfur and phosphorus sulfide lithium battery. Several all-solid-state sulfur and phosphorus sulfide lithium batteries are adhesively stacked together with epoxy resin to form a group of all-solid-state sulfur and phosphorus sulfide lithium batteries. Fabricate a graphene electrode lead-out component: Mix graphene powder with an organic binder and put it into a mold, heat the mold and extrude the graphene powder in the mold, and after cooling, take out the solid graphene plate with a solid graphene rod. Coat the inner surface of one end of a carbon fiber braided tube with a layer of epoxy resin, then put the end on the solid graphene rod and heat it to cure. Then fill the carbon fiber braided tube with graphene powder and compact it. Insert the tip of a solid graphene plug adhesively bonded with epoxy resin into the other end of the carbon fiber braided tube. Finally, put an insulating sleeve outside the carbon fiber braided tube to become a graphene electrode lead-out component. Use epoxy resin to bond the solid graphene plate of a graphene electrode lead-out component under the graphene positive electrode film of the lowermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries, and use epoxy resin to bond the solid graphene plate of a graphene electrode lead-out component on the graphene negative electrode film of the uppermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries, and then heat it to cure. Before charging and discharging, microwave is introduced into the metal container of the vehicle chassis containing the all-solid-state sulfur and phosphorus sulfide lithium battery. The blades of the electric microwave stirrer in the glass sandwich on the top of the metal container of the vehicle chassis rotate to stir the microwave in the metal container of the vehicle chassis, and cool the all-solid-state lithium battery in the metal container of the vehicle chassis. Microwave controls the chemical reactions inside the all-solid-state sulfur and phosphorus sulfide lithium battery and the temperature inside the all-solid-state sulfur and phosphorus sulfide lithium battery.The chemical reaction process of charging and discharging a all-solid-state lithium battery is a process of electron transfer. Microwaves cause electrons to oscillate during movement, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. It's like the extrusion piles used in infrastructure construction, where not only pressure but also vibration is applied to the pile so that it can be smoothly inserted into the soil. The graphene film of the all-solid-state lithium battery has a large number of free electrons, which oscillate under the action of microwaves to generate heat. The internal temperature of the all-solid-state lithium battery rises, and the internal energy of various substances in the all-solid-state lithium battery increases, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. Lithium atoms in lithium silicide ceramics are in-situ solidified, and lithium atoms in lithium silicide ceramics do not break away from the bondage of silicon atoms during the chemical reaction process. The all-solid-state sulfur and phosphorus sulfide lithium battery can be normally charged and discharged at 60 °C, and the operating range of the all-solid-state sulfur and phosphorus sulfide lithium battery is -10 °C to 105 °C. Sulfur does not chemically react with lithium at room temperature of 20 °C, but sulfur can smoothly chemically react with lithium at room temperature of 60 °C. Phosphorus sulfide in the solid-state phosphorus sulfide lithium battery slowly chemically reacts with oxygen in the air when exposed to the air at a temperature above 39 °C. Therefore, the all-solid-state sulfur and phosphorus sulfide lithium battery is safer than the all-solid-state black phosphorus and phosphorus sulfide lithium battery.
[0009] A microwave-controlled all-solid-state lithium battery. The all-solid-state black phosphorus and phosphorus sulfide lithium battery, from bottom to top in sequence, consists of a graphene positive electrode film, the first layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, the first layer of lithium silicide ceramic powder, the first layer of graphene film, the second layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, the second layer of lithium silicide ceramic powder, the second layer of graphene film, the third layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, the third layer of lithium silicide ceramic powder, the third layer of graphene film, the fourth layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, the fourth layer of lithium silicide ceramic powder, the fourth layer of graphene film, the fifth layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, the fifth layer of lithium silicide ceramic powder, and a graphene negative electrode film. The graphene electrode lead-out component is composed of a solid graphene plate, a solid graphene rod, a carbon fiber braided tube, graphene powder, an insulating sleeve, and a solid graphene plug. The size of the solid graphene plate is the same as that of the graphene positive electrode film or the graphene negative electrode film. The edge of the solid graphene plate is connected to the solid graphene rod. One end of the carbon fiber braided tube is fixed on the graphene rod. The carbon fiber braided tube is filled with graphene powder. An insulating sleeve is sleeved outside the carbon fiber braided tube. The tip of the solid graphene plug is inserted into the other end of the carbon fiber braided tube. The upper surface border of the graphene positive electrode film, the upper surface border of the first layer of graphene film, the upper surface border of the second layer of graphene film, the upper surface border of the third layer of graphene film, and the upper surface border of the fourth layer of graphene film are all coated with raw butylbenzene rubber. The lower surface border of the first layer of graphene film, the lower surface border of the second layer of graphene film, the lower surface border of the third layer of graphene film, the lower surface border of the fourth layer of graphene film, and the lower surface border of the graphene negative electrode film are all coated with raw butylbenzene rubber. The black phosphorus and phosphorus sulfide solid electrolyte containing lithium iodide is the positive electrode material of the all-solid-state black phosphorus and phosphorus sulfide lithium battery, and the lithium silicide ceramic powder is the negative electrode material of the all-solid-state black phosphorus and phosphorus sulfide lithium battery. Heat the solid sulfur lithium battery to 150 °C to cure the raw butylbenzene rubber. The all-solid-state black phosphorus and phosphorus sulfide lithium battery can be normally charged and discharged at 60 °C, and the operating range of the all-solid-state black phosphorus and phosphorus sulfide lithium battery is -10 °C to 105 °C. Place the all-solid-state black phosphorus and phosphorus sulfide lithium battery in a metal container on the vehicle chassis. One end of the metal container on the vehicle chassis has an air inlet window, and a stainless steel wire mesh is installed on the air inlet window. The air duct connected from the blower is connected to the air inlet window; the other end of the metal container on the vehicle chassis has an air outlet window, and a stainless steel wire mesh is installed on the air outlet window, and an air outlet duct is installed on the air outlet window. A glass sandwich is installed on the top of the metal container on the vehicle chassis, and the blades of an electric microwave stirrer are inside the glass sandwich installed on the top of the metal container on the vehicle chassis. Before charging and discharging, introduce microwaves into the metal container on the vehicle chassis containing the all-solid-state black phosphorus and phosphorus sulfide lithium battery to control the chemical reaction inside the all-solid-state black phosphorus and phosphorus sulfide lithium battery and increase the temperature inside the all-solid-state sulfur and phosphorus sulfide lithium battery.
[0010] A microwave-controlled all-solid-state lithium battery. Ethanol is used to blend a powder containing 5% lithium iodide, 75% black phosphorus, and 20% phosphorus sulfide to form a slurry of black phosphorus and phosphorus sulfide containing lithium iodide. Lithium iodide can reduce the internal resistance of the all-solid-state black phosphorus and phosphorus sulfide lithium battery. Ethanol is used to blend lithium silicide ceramic powder to form a lithium silicide ceramic slurry. A slurry of black phosphorus and phosphorus sulfide containing lithium iodide is coated on the upper surface of the graphene positive electrode film, the upper surface of the first graphene film, the upper surface of the second graphene film, the upper surface of the third graphene film, and the upper surface of the fourth graphene film. A raw butylbenzene rubber is coated on the upper surface border of the graphene positive electrode film, the upper surface border of the first graphene film, the upper surface border of the second graphene film, the upper surface border of the third graphene film, and the upper surface border of the fourth graphene film. A lithium silicide ceramic slurry is coated on the lower surface of the first graphene film, the lower surface of the second graphene film, the lower surface of the third graphene film, the lower surface of the fourth graphene film, and the lower surface of the graphene negative electrode film. The graphene positive electrode film, the first graphene film, the second graphene film, the third graphene film, the fourth graphene film, and the graphene positive electrode film are stacked and bonded together, and heated to 150 °C to cure the raw butylbenzene rubber and vaporize the ethanol, forming an all-solid-state black phosphorus and phosphorus sulfide lithium battery. Several all-solid-state black phosphorus and phosphorus sulfide lithium batteries are bonded and stacked together with epoxy resin to form a group of all-solid-state black phosphorus and phosphorus sulfide lithium batteries. Fabricate a graphene electrode lead-out component: Mix graphene powder with an organic binder and place it in a mold. Heat the mold and extrude the graphene powder in the mold. After cooling, take out the solid graphene plate with a solid graphene rod. Coat the inner surface of one end of a carbon fiber braided tube with a layer of epoxy resin, then slip this end over the solid graphene rod and heat to cure. Then fill the carbon fiber braided tube with graphene powder and compact it. Insert the tip of a solid graphene plug bonded with epoxy resin into the other end of the carbon fiber braided tube. Finally, slip an insulating sleeve over the carbon fiber braided tube to form a graphene electrode lead-out component. Bond the solid graphene plate of a graphene electrode lead-out component to the lower surface of the graphene positive electrode film of the lowermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries with epoxy resin, and bond the solid graphene plate of a graphene electrode lead-out component to the upper surface of the graphene negative electrode film of the uppermost all-solid-state phosphorus sulfide lithium battery in a group of all-solid-state phosphorus sulfide lithium batteries with epoxy resin, and then heat to cure. Before charging and discharging, microwave is introduced into the metal container of the vehicle chassis containing the all-solid-state black phosphorus and phosphorus sulfide lithium battery. The blades of the electric microwave stirrer in the glass sandwich on the top of the vehicle chassis metal container rotate to stir the microwave in the vehicle chassis metal container, and cool the all-solid-state lithium battery in the vehicle chassis metal container. Microwave controls the chemical reactions inside the all-solid-state black phosphorus and phosphorus sulfide lithium battery, as well as the temperature inside the all-solid-state black phosphorus and phosphorus sulfide lithium battery.The chemical reaction process of charging and discharging a all-solid-state lithium battery is a process of electron transfer. Microwaves will cause electrons to oscillate during movement, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. Just like the extrusion piles used in infrastructure construction, not only pressure but also vibration needs to be applied to the piles so that they can be smoothly inserted into the soil. The graphene film of the all-solid-state lithium battery has a large number of free electrons, and heat is generated by oscillation under the action of microwaves. The internal temperature of the all-solid-state lithium battery rises, and the internal energy of various substances in the all-solid-state lithium battery increases, assisting the chemical reaction of charging and discharging the all-solid-state lithium battery. Lithium atoms in lithium silicide ceramics are in-situ solidified, and lithium atoms in lithium silicide ceramics will not break away from the bondage of silicon atoms during the chemical reaction process. The all-solid-state sulfur and phosphorus sulfide lithium battery can be normally charged and discharged at 60 °C, and the operating range of the all-solid-state sulfur and phosphorus sulfide lithium battery is -10 °C to 105 °C. Black phosphorus does not chemically react with lithium at room temperature of 20 °C, but it can smoothly chemically react with lithium at room temperature of 60 °C. Phosphorus sulfide in the solid-state lithium battery with phosphorus sulfide slowly chemically reacts with oxygen in the air when exposed to the air at a temperature exceeding 39 °C. Therefore, the all-solid-state black phosphorus and sulfur phosphorus sulfide lithium battery is safer than the all-solid-state black phosphorus and phosphorus sulfide lithium battery.
Claims
1. A microwave-controlled all-solid-state lithium battery, wherein the all-solid-state phosphorus sulfide lithium battery comprises, from bottom to top, a graphene positive electrode film, a first layer of phosphorus sulfide powder containing lithium iodide, a first layer of lithium silicide ceramic powder, a first layer of graphene film, a second layer of phosphorus sulfide powder containing lithium iodide, a second layer of lithium silicide ceramic powder, a second layer of graphene film, a third layer of phosphorus sulfide powder containing lithium iodide, a third layer of lithium silicide ceramic powder, a third layer of graphene film, a fourth layer of phosphorus sulfide powder containing lithium iodide, a fourth layer of lithium silicide ceramic powder, a fourth layer of graphene film, a fifth layer of phosphorus sulfide powder containing lithium iodide, a Five layers of lithium silicide ceramic powder, graphene negative electrode film, graphene electrode lead-out element consists of solid graphene plate, solid graphene rod, carbon fiber braided tube, graphene powder, insulating sleeve, solid graphene plug. The size of the solid graphene plate is the same as that of the graphene positive electrode film or the graphene negative electrode film. The edge of the solid graphene plate is connected to the solid graphene rod. One end of the carbon fiber braided tube is fixed on the graphene rod. The carbon fiber braided tube is filled with graphene powder. The carbon fiber braided tube is covered with an insulating sleeve. The tip of the solid graphene plug is inserted into the other end of the carbon fiber braided tube. The upper surface frame of the graphene positive electrode film, the upper surface frame of the first layer of graphene film, the upper surface frame of the second layer of graphene film, the upper surface frame of the third layer of graphene film, and the upper surface frame of the fourth layer of graphene film are all coated with butylbenzene rubber raw material, the lower surface frame of the first layer of graphene film, the lower surface frame of the second layer of graphene film, the lower surface frame of the third layer of graphene film, the lower surface frame of the fourth layer of graphene film, and the lower surface frame of the graphene negative electrode film are all coated with butylbenzene rubber raw material, the phosphorus sulfide solid electrolyte containing lithium iodide is the positive electrode material of the all-solid-state phosphorus sulfide lithium battery, and the lithium silicide ceramic powder is the all-solid The solid-state sulfur lithium sulfide battery negative electrode material is heated to 150°C to solidify the butylbenzene rubber raw material rubber; the all-solid-state phosphorus sulfide lithium battery can only be normally charged and discharged at 60°C, and the use range of the all-solid-state phosphorus sulfide lithium battery is -10°C to 105°C. The all-solid-state phosphorus sulfide lithium battery is in a metal container of the automobile chassis, and an air inlet window is provided at one end of the automobile chassis metal container, and a stainless steel wire mesh is installed on the air inlet window, and the air duct connected from the blower is connected to the air inlet window water; the other end of the automobile chassis metal container has an air outlet window, a stainless steel wire mesh is installed on the air outlet window, and an air outlet duct is installed on the air outlet window; the characteristics are: A glass interlayer is installed on the top of the metal container of the automobile chassis. The glass interlayer installed on the top of the metal container of the automobile chassis contains blades of an electric microwave stirrer. Microwaves are introduced into the metal container of the automobile chassis containing the all-solid-state lithium phosphorus sulfide battery before charging and discharging to control the chemical reaction inside the all-solid-state lithium phosphorus sulfide battery and to increase the temperature inside the all-solid-state lithium phosphorus sulfide battery.
2. A microwave-controlled all-solid-state lithium battery, wherein the all-solid-state sulfur and phosphorus sulfide lithium battery is composed of a graphene positive electrode film, a first layer of powder containing lithium iodide and phosphorus sulfide, a first layer of lithium silicide ceramic powder, a first layer of graphene film, a second layer of powder containing lithium iodide and phosphorus sulfide, a second layer of lithium silicide ceramic powder, a second layer of graphene film, a third layer of powder containing lithium iodide and phosphorus sulfide, a third layer of lithium silicide ceramic powder, a third layer of graphene film, a fourth layer of powder containing lithium iodide and phosphorus sulfide, a fourth layer of lithium silicide ceramic powder, a fourth layer of graphene film, a fifth layer of powder containing lithium iodide and phosphorus sulfide Powder, fifth layer of lithium silicide ceramic powder, graphene negative electrode film, graphene electrode lead-out element is composed of solid graphene plate, solid graphene rod, carbon fiber braided tube, graphene powder, insulating sleeve, solid graphene plug, the size of solid graphene plate is the same as that of graphene positive electrode film or graphene negative electrode film, the edge of solid graphene plate is connected with solid graphene rod, one end of carbon fiber braided tube is fixed on graphene rod, carbon fiber braided tube is filled with graphene powder, and the outside of carbon fiber braided tube is covered with insulating sleeve, the tip of solid graphene plug is inserted into the other end of carbon fiber braided tube, stone The upper surface frame of the graphene positive electrode film, the upper surface frame of the first graphene film, the upper surface frame of the second graphene film, the upper surface frame of the third graphene film, and the upper surface frame of the fourth graphene film are all coated with butylbenzene rubber raw material, the lower surface frame of the first graphene film, the lower surface frame of the second graphene film, the lower surface frame of the third graphene film, the lower surface frame of the fourth graphene film, and the lower surface frame of the graphene negative electrode film are all coated with butylbenzene rubber raw material, the solid electrolyte containing lithium iodide and phosphorus sulfide is an all-solid-state phosphorus sulfide lithium battery positive electrode material, and the lithium silicide ceramic powder is an all-solid-state sulfur sulfide The negative electrode material of the phosphorus-lithium battery, the solid-state sulfur-lithium battery is heated to 150°C to solidify the butylbenzene rubber raw material; the all-solid-state sulfur and sulfur-phosphorus-sulfide lithium battery can only be normally charged and discharged at 60°C, and the use range of the all-solid-state sulfur and sulfur-phosphorus-sulfide lithium battery is -10°C to 105°C. The all-solid-state sulfur and sulfur-phosphorus-sulfide lithium battery is in a metal container of the automobile chassis, and there is an air inlet window at one end of the automobile chassis metal container, and a stainless steel wire mesh is installed on the air inlet window, and the air duct connected from the blower is connected to the air inlet window water; there is an air outlet window at the other end of the automobile chassis metal container, and a stainless steel wire mesh is installed on the air outlet window, and an air outlet duct is installed on the air outlet window; it is characterized in that: The positive electrode material of the all-solid-state sulfur and phosphorus sulfide lithium battery is a sulfur solid electrolyte containing lithium iodide and phosphorus sulfide. A glass interlayer is installed on the top of the automobile chassis metal container. The glass interlayer installed on the top of the automobile chassis metal container has blades of an electric microwave stirrer. Before charging and discharging, microwaves are introduced into the automobile chassis metal container containing the all-solid-state sulfur and phosphorus sulfide lithium battery to control the chemical reaction inside the all-solid-state sulfur and phosphorus sulfide lithium battery and increase the temperature inside the all-solid-state sulfur and phosphorus sulfide lithium battery.
3. A microwave-controlled all-solid-state lithium battery, wherein the all-solid-state black phosphorus and phosphorus sulfide lithium battery is composed of a graphene positive electrode film, a first layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, a first layer of lithium silicide ceramic powder, a first layer of graphene film, a second layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, a second layer of lithium silicide ceramic powder, a second layer of graphene film, a third layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, a third layer of lithium silicide ceramic powder, a third layer of graphene film, a fourth layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, a fourth layer of lithium silicide ceramic powder, a fourth layer of graphene film, a fifth layer of black phosphorus and phosphorus sulfide powder containing lithium iodide, a Phosphorus and phosphorus sulfide powder, fifth layer lithium silicide ceramic powder, graphene negative electrode film, graphene electrode lead-out element is composed of solid graphene plate, solid graphene rod, carbon fiber braided tube, graphene powder, insulating sleeve, solid graphene plug, the size of solid graphene plate is the same as that of graphene positive electrode film or graphene negative electrode film, the edge of solid graphene plate is connected with solid graphene rod, one end of carbon fiber braided tube is fixed on graphene rod, carbon fiber braided tube is filled with graphene powder, and the outside of carbon fiber braided tube is covered with insulating sleeve, the tip of solid graphene plug is inserted into the other end of carbon fiber braided tube, stone The upper surface frame of the graphene positive electrode film, the upper surface frame of the first graphene film, the upper surface frame of the second graphene film, the upper surface frame of the third graphene film, and the upper surface frame of the fourth graphene film are all coated with butylbenzene rubber raw material, the lower surface frame of the first graphene film, the lower surface frame of the second graphene film, the lower surface frame of the third graphene film, the lower surface frame of the fourth graphene film, and the lower surface frame of the graphene negative electrode film are all coated with butylbenzene rubber raw material, the black phosphorus and phosphorus sulfide solid electrolyte containing lithium iodide is an all-solid-state black phosphorus and phosphorus sulfide lithium battery positive electrode material, and the lithium silicide ceramic powder is an all-solid-state black phosphorus and The negative electrode material of the lithium sulfide phosphorus battery is to heat the solid-state lithium sulfide battery to 150°C to solidify the butylbenzene rubber raw material; the all-solid-state black phosphorus and lithium sulfide phosphorus battery can only be normally charged and discharged at 60°C, and the use range of the all-solid-state black phosphorus and lithium sulfide phosphorus battery is -10°C to 105°C. The all-solid-state black phosphorus and lithium sulfide phosphorus battery is in a metal container of the automobile chassis, and there is an air inlet window at one end of the metal container of the automobile chassis, and a stainless steel wire mesh is installed on the air inlet window, and the air duct connected to the blower is connected to the air inlet window water; there is an air outlet window at the other end of the metal container of the automobile chassis, and a stainless steel wire mesh is installed on the air outlet window, and an air outlet duct is installed on the air outlet window; the characteristics are: A glass interlayer is installed on the top of the metal container of the automobile chassis. The glass interlayer installed on the top of the metal container of the automobile chassis contains blades of an electric microwave stirrer. Microwaves are introduced into the black container of the automobile chassis containing the all-solid-state black and lithium phosphorus sulfide battery before charging and discharging to control the chemical reaction inside the all-solid-state black and lithium phosphorus sulfide battery and to increase the temperature inside the all-solid-state sulfur and lithium phosphorus sulfide battery.